Psychiatric Referrals in a Tertiary Care Hospital in North India: A Retrospective Study - Akansha Bhardwaj; Dimple Gupta; Rashmi Prakash; Nimmi A. Jose (Archives of Medicine and Health Sciences, 2024)
Background and Aim: There is high prevalence of mental disorders in specialist treatment seekers across specialties. Still, psychiatry referral rates have been found to be very low. A physician refers a patient to psychiatric services for reasons like known case of mental disorder, physical symptoms without adequate explanation, or if the physician feels inadequate in dealing with psychological symptoms. A multi disciplinary approach should be encouraged for the management of such patients, facilitating early recognition and management of psychiatric problems. The aim is to study the sociodemographic variables of psychiatric referrals, reasons and diagnostic categories of psychiatric referrals, and the distribution of psychiatric diagnoses according to reasons and sources of referrals. Materials and Methods: A retrospective hospital based study was conducted in the Department of Psychiatry, Hamdard Institute of Medical Sciences and Research, New Delhi, by analyzing the recorded data of referrals to the Psychiatry Department from various other specialties from January 2019 to March 2020. All referred patients were evaluated by a Psychiatrist (MD Psychiatry) and the diagnosis was made as per the International Statistical Classification of Diseases 10 criteria. The data obtained were analyzed using descriptive statistical methods. Results: This study included 315 psychiatric referrals. The mean age and standard deviation of the entire sample were 37.75 ± 17.63. The referral rate was minimum from January to March 2020. The highest number of referrals was from Medicine Department (66.3%). Among those, the most common diagnoses were that of alcohol dependence (27%). The most common overall reason for referral was substance use (26.2%). The most common psychiatric diagnosis was alcohol dependence (24%). Hypertension was the most common physical comorbidity. The most common diagnosis for known case of psychiatric illness and follow ups were psychotic disorders (27.3% and 26.3%). Conclusion: The findings of this study give us insight that consultation liaison psychiatry should focus on early recognition and wholesome management of psychiatric disorders in patients with physical illness through consultation psychiatry services in general hospital settings.